MENGUKUR KINERJA PEMASARAN: KAJIAN KONSEPTUAL PERKEMBANGAN TEORI - Ahmad Yahya Surya Winata (Jurnal Riset AKuntansi dan Bisnis, 2010)
This paper aims to examine some overview the development of the marketingperformance concept and seeks to develop a comprehensive model for measuringmarketing performance. Marketing performance was initially measured in terms of'efficiency' and sometimes referred to 'productivity' is calculated by comparing thecost of marketing input to output on the level of sales. This indicator measures howefficient of marketing programs in the company based on financial measurements.But we realize that the performance-based marketing with financial indicatorsturned out to contain a lot of weaknesses, including short-term perspective, it cangive rise to organizational conflicts of interest between the company and itsemployees, and in the long term consciously or not, can obscure the achievement ofthe vision and mission including company philosophy. Furthermore, in the 1990s,many scholars developed a set of indicators to measure marketing performance,including customer satisfaction and customer loyalty. Both indicators is morerelevant for measuring marketing performance today that allow improvement qualityencourage and products value, service quality and customer relationship techniques.Even indicators that can not be measured by monetary value be recognized and notignored by the company. The next concept that developed was the marketingperformance measurement indicators of brand equity, which measures howpowerfull brand to attract consumers in choosing a product. With the success of thisindicator can be seen positioning and differentiation are expected by the companytoward market to establish the value of the firm.Developing conceptual model of marketing performance in this paper isfocused on the discussion of marketing performance indicators developed by thescholars’ disagreements over the concepts that are presented, and finally arranged amodel that describes the comprehensive marketing performance indicators.Current concepts in the journal which is used as the main reference in thispaper on marketing performance measurement as described above in principleemphasizes on the development of non-financial indicators consisting of marketshare, customer satisfaction, loyalty or customer retention, brand equity, andinnovation in the development can affect the improvement of corporate value (thevalue of the firm) as a financial indicator. It is proposed to review the entry point isthe development of non-financial measures will affect the value of the company.